A beta-alpha coincidence counting system for measurement of trace quantities of 238U and 232Th in aqueous samples at the Sudbury Neutrino Observatory. (18th August 2016) - Dawson, M.; Doucas, G.; Fergani, H.; Jelley, N.A.; Majerus, S.; O'Keeffe, H.M.; Peeters, S.J.M.; Perry, C.
Abstract: The Sudbury Neutrino Observatory experiment was built to measure the total flux of 8 B solar neutrinos via the neutral current disintegration deuterium nuclei. This process can be mimiced by daughter isotopes of 232 Th and 238 U which can photodisintegrate the deuterium nucleus. Measurement of the concentration of such radioisotopes in the heavy water was critical to the success of the experiment. A radium assay technique using Hydrous Titanium Oxide coated filters was developed for this purpose and it was used in conjunction with a delayed beta-alpha coincidence counting system. The design, calibration and operation of this counting system are described in this paper. The counting efficiency for 232 Th ( 224 Ra) and 238 U ( 226 Ra) were measured to be 50 ± 5 % and 62 ± 7 %